Shareholder wealth vs. stakeholder interests? Evidence from code compliance under the German corporate governance code - Brigitte Haar (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
In order to better differentiate the drivers of corporations' actions, in particular shareholder wealth and stakeholder interests, the paper explores the significance of the comply or explain-principle and its underlying enforcement mechanisms more generally. Against this background, compliance rates with specific provisions may shed a light on companies' reasons for following the code. An analysis of these rates at the example of distinct provisions of the German Corporate Governance Code is therefore entered into. In light of the current corporate governance debate and the legitimacy problems that are raised, among the code provisions that exemplify these questions very well are those regulating incentive pay, severance pay caps, and age limits for supervisory board members. Their analysis will lay a basis for an answer to the question about what motivates companies to comply with the code. The motivation then paves the way to arrive at a further specification of the determinants of the regulatory evolution of the Code and the range of stakeholders and their concerns that enter into it.
urn:nbn:de:hebis:30:3-424227
Keywords: G38; K20; M12; M14; M52; 330; corporate governance codes; soft law; stakeholder; shareholder wealth; market enforcement; German corporate governance; supervisory board; incentive pay; severance pay caps; age limits